The Role of the Principal in Creating Effective School - Yasifun Yasifun; Budi Haryanto; Istikomah Istikomah (International Consortium of Education and Culture Research Studies, 2020)
This study aims to describe the role of the principal in creating an effective school at SMA Al Fattah Buduran Sidoarjo. The method used to determine the informant is purposive aside. In this qualitative research data collection, the authors use the interview, documentation and observation methods. From the results of this study, it was concluded that the Principal played a role in creating an effective school at Al Fattah Buduran Sidoarjo High School. Effective schools are schools that have good management standards, are transparent, are responsive, and accountable, and are able to empower every important component of the school. This is proven by Al Fattah High School continuing to experience an increase in the number of students, facilities and infrastructure, as well as their achievements.